Representations of the Metaverse in the Works of Potter Jason Walker (Al-Academy, 2023)
The current research studies (representations of metaphysics in the works of potter Jason Walker) a concept that refers to To a large extent, by conveying a sense of reality to the recipient by conveying ideas, contents, and connotations. A variety of center hit, dispersion, and rejection of everything that prevails, so our position on the closed text has shifted To the open text, through the role played by cross-pollination in the works of the potter (Jason Walker), which established a clear hypothetical vision of the image represented in the construction of the ceramic work and the thought that was embodied in that image represented by the nature of its unrealistic formations for those ceramic artworks. It is thus considered a logical alternative to shake the previous structures and to find New structures thanks to new technical installations. The research included four chapters, the first chapter concerned the research problem and its importance And the need for it and the aim of the research (to know the representations of the meta virus in the works of Jason Walker), as well as included. Contemporary ceramic works by potter Jason - the chapter includes temporal boundaries for the period from (2009-2020) and Walker, which were completed in America, and the chapter also included a definition of the most important search terms. And he studied. The second chapter, the theoretical framework and previous studies, consists of two sections, the first section. It included (metaverse - cognitive), and the second topic was divided into two axes, the first of which dealt with (Artistic and aesthetic approaches in contemporary ceramics) The second axis dealt with. Contemporary (b- potter style Jason Walker), and the chapter ended with indicators of the theoretical framework and previous studies. The third chapter included the research procedures, as it included the framework of the research community and the adult.